Silence in teaching and learning: A proposed task for teachers to be silent in reading class - Nguyen, Thanh Thai (Technium Social Sciences Journal, 2024)
In most second-language classrooms, students are expected and encouraged to spend a significant amount of classroom time speaking. However, students’ passivity in learning is not only a root of silence, but teachers’ classroom styles are also viewed as a major cause of learner silence. This leads to the necessary need for teachers to have a good understanding of silence as a pedagogy that can motivate silent or reticent students to be active and to speak more. This implies that teacher plays an important role in motivating the silent students’ learning by keeping silent students from feelings of being shy, ignorant or rebellious. For these reasons, this paper is going to review some viewpoints on silence and propose a task of using silence in reading class which the teachers of English can apply in their reading class.